2014
DOI: 10.1038/nn.3687
|View full text |Cite
|
Sign up to set email alerts
|

Attentive scanning behavior drives one-trial potentiation of hippocampal place fields

Abstract: The hippocampus is thought to play a critical role in episodic memory by incorporating the sensory input of an experience onto a spatial framework embodied by place cells. Although the formation and stability of place fields requires exploration, the interaction between discrete exploratory behaviors and the specific, immediate, and persistent modifications of neural representations required by episodic memory has not been established. We recorded place cells in rats and found that increased neural activity du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
151
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(161 citation statements)
references
References 51 publications
6
151
0
Order By: Relevance
“…The reverse was true when space was relevant. Taken together with recent evidence suggesting that place fields can be induced by attentive scanning (Monaco et al 2014), the findings point to selective attention, and not merely general arousal, as a major determinant of experiencedependent stabilization of hippocampal place maps.…”
Section: Memory Encodingsupporting
confidence: 70%
See 1 more Smart Citation
“…The reverse was true when space was relevant. Taken together with recent evidence suggesting that place fields can be induced by attentive scanning (Monaco et al 2014), the findings point to selective attention, and not merely general arousal, as a major determinant of experiencedependent stabilization of hippocampal place maps.…”
Section: Memory Encodingsupporting
confidence: 70%
“…Of the 12 cells that he recorded, 10 appeared to have spatial firing fields immediately, supporting the idea that the place-cell map was largely predetermined. Subsequently, studies with larger ensembles of cells found that place fields often took several minutes of exploration before settling into a stable firing field (McNaughton and Wilson 1993;Frank et al 2004) and the formation of new and stable place fields was dependent on the animal's behavior and attention to the spatial features of the environment (Kentros et al 2004;Monaco et al 2014). These results point to a critical role for experience in forming the hippocampal map of space.…”
Section: Place Cells Synaptic Plasticity and Memorymentioning
confidence: 99%
“…On one hand, scanning the possible routes to take allows acquiring sensory information regarding the environmental options. This increase in available sensory information could potentially increase the number of hippocampal place-cells tuned to the spatial locations of each of the maze-arms, as observed in 9 , thereby optimizing performance. On the other hand, aligning one's body towards possible decision options would allow the setting of path-integration hippocampal mechanisms to simulate future trajectories, as has been theoretically and computationally postulated 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…As expected, we have observed greater trajectory duration, length and IdPhi for the low-frequency condition when compared to the high-frequency condition, suggesting that frequency of exposure modulates the internal representation of the environment and/or experimental contingencies. Head-scanning behaviors have been observed to increase the activity of hippocampal place-cells leading to the potentiation of their receptive-fields at a given spatial location 9 . These results suggest one-trial encoding of experiences mediated by place-cell activity.…”
Section: Vte Decreases With Learningmentioning
confidence: 99%
See 1 more Smart Citation